The scientific academic journal article: Guidelines for planning and editing according to the APA model - Camacho Villalobos, María Elena (2014)
This article was based on the authors´ experience as directors and editors of academic journals, participation in editorial committees, text arbitration, dictated lessons on article writing and writing in general and philological evaluation. Through these experiences, the authors have detected many difficulties in the writing of an article; therefore, they purpose a set of quality indicators and relevant information regarding the selection of the publication mode, general format, types and parts of the article; the construction of cohesiveness and coherence; text planification and paraphrase construction. They outline the elements that should be checked over before submitting an article as well as the estrategies to present it to a journal. With all these, they tend to details related to the article´s formal and pragmatic means. Both synthesis and analysis become tools for the development of paraphrasing; and therefore, approaching them has been considered relevant, mainly because it enables the gathering of information coming from diverse sources and its adequate utilization in a document. Finally, they emphasize the idea that writing is an act of communication through which, the author should colaborate with the potential readers offering them a cohesive, coherent, concise and plain text.